Patristic studies in the twenty-first century: proceedings of an International Conference to Mark the 50th Anniversary of the International Association of Patristic Studies - Bitton-Ashkelony, Bruria; De Bruyn, Theodore; Harrison, Carol (Brepols, 2015)
An overview of the state of Patristic studies world-wide, in the twenty-first century: its relevance and contribution to the fields of religious culture, traditions, literature, art, archaeology and theology. To mark the fiftieth anniversary of its inception, the International Association of Patristic Studies, in collaboration with the Center for the Study of Christianity in the Hebrew University of Jerusalem, convened an international conference in Jerusalem on 25th - 27th June, 2013. The theme of the conference was the state of patristic studies in the twenty-first century, focusing on the implications of the various settings and interests of patristic studies for the future of the field.--
Includes bibliographical references
Keywords: Konferenzschrift -- 2013 -- Jerusalem; Festschrift; Geschichte 1900-2000; Vätertheologie; Patristik